Nazrul’s Persia in his decolonizing melodies - Nizam Uddin, Md Abu Saleh (IIUC Studies, 2022)
Kazi Nazrul Islam of Bangla literature may be best described as a poet of humanity. Besides the anti-colonial and spiritual dimensions of his melodies, there is also a decolonizing tone in his literature. His songs, especially those that recuperate and include rich Persian heritage of Bangla literature, significantly contribute to decolonizing the colonially victimized Bangla literature in British India. Thus, this paper initially attempts to examine how distinctly and strongly Persian language, nature and culture remain as an important heritage for Bangla literature while Nazrul writes songs imbued with the Persian elements. Then, this paper has the prime aim to explore how the poet, in a colonial backdrop, robustly endeavors a comprehensive decolonization of Bangla literature with his Persia-attached songs. Thus, the study examines the poet’s measures of decolonization with efforts to revive successful Bangla literature, have it compete with or even exceed English literature and place Bengali Muslims again in their rightful literary domain. IIUC Studies Vol.18, December 2021: 135-156